Pudendal Nerve Block with Bupivacaine Vs Bupivacaine Plus Steroid on Reducing Perianal Pain After Hemorrhoidectomy - Rafiq, Tehmina; Ali, Mansab; Usman, Amir; Shafiq, Umer; Ara, Seemab; Tayyab, Syed Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Postoperative pain management in hemorrhoidectomy remains a clinical challenge, with pudendal nerve block (PNB) emerging as an effective technique. Adding steroids to local anaesthetics may enhance analgesic efficacy and prolong pain relief. Objective: To compare the effectiveness of pudendal nerve block (PNB) using bupivacaine alone versus bupivacaine with dexamethasone in reducing perianal pain following hemorrhoidectomy. Methods: A prospective study was conducted at the Department of General Surgery, University of Lahore Teaching Hospital, Lahore, from July 31, 2024, to January 30, 2025. A total of 60 patients undergoing hemorrhoidectomy were randomly assigned into two groups: Group A (n=30) received PNB with 20 mL bupivacaine. Group B (n=30) received PNB with 20 mL bupivacaine and 8 mg dexamethasone. The blocks were performed bilaterally under spinal anaesthesia using anatomical landmarks. All patients received standard postoperative analgesia. Pain scores were recorded at 12 and 24 hours postoperatively using the Visual Analog Scale (VAS). Group comparisons were conducted using the t-test, with statistical significance at p ≤ 0.05. Results: The mean pain score at 12 hours postoperatively was significantly lower in Group B (1.90 ± 0.481) compared to Group A (2.47 ± 0.681), with a p-value of 0.001, indicating a statistically significant difference in pain relief. The addition of dexamethasone resulted in enhanced and prolonged analgesia without increasing adverse effects. Conclusion: The use of PNB with bupivacaine plus dexamethasone significantly reduces postoperative perianal pain after hemorrhoidectomy compared to bupivacaine alone. This combination provides superior analgesic efficacy and can be considered a safe and effective technique for pain management in perianal surgeries.